Broadcasting of violence on Lithuanian television programs - Kiguolytė, Rugilė; Valickas, Gintautas (Psichologija, 2008)
Constant demonstration of violence and aggressive models on television threatens to the safety of the society, as by this a young person’s knowledge of the world is perverted and the usage of aggressive behaviour is stimulated. The purpose of the present research was to identify the violence demonstrated on the main Lithuanian TV channels (LRT, LNK, TV3). For data collecting we were using a DVD player, which was programmed to record random 15-minute episodes three times per day on different TV channels on October and November in 2006 and on January, 2007. The total material contained 18 hours of recording. 194 occasions of violence captured were evaluated according to the criteria developed by the authors of this paper. It was looked at the type of the violence demonstrated, the complexion and purpose of the demonstration of the violence, the degree of its gravity and particularity, the final effects of the violence demonstrated, the presented evaluation of the violence and the frequency of violence acts in different channels and programs at different times of the day. Besides the authors of this paper, two independent members from the Board of Experts of the Office of the Inspector of Journalists Ethics were asked to evaluate the violence acts according to developed criteria. The results revealed that the average frequency of broadcasting violence on TV is 10.8 violence acts per hour. The highest frequency of broadcasting violence was on TV3 channel – it makes 16.3 violence acts per hour, while LRT channel had least rate of violence – 6 acts per hour (p ≤ 0.001). Most violence acts (38.1 percent) were recorded from 18.00 to 23.00 h, least (25.8 percent) – from 6.00 to 12.00 h (p ≤ 0.031). In this general complexion of all Lithuanian programs the most frequent is physical violence and both – physical and psychical – types of violence are shown only with a reason to call emotions and viewers attention to television. 46 percent of violent acts were demonstrated without any noticeable ravage to victim and 49 percent there were no clear evaluation of the violent act or aggressor itself. Contrarily, violent behavior was shown to bring positive after-effect to the aggressor. It was also noticed that the biggest number of physical and psychical violence acts occurs in cartoons, which is significantly different from the number of violence acts demonstrated in feature films (p ≤ 0.001) and during the announcements (p ≤ 0.024). As cartoons are aimed at the audience of children of the preschool age and early school age, the conclusion can be drawn that the youngest and the most sensitive group of habitants in our country is under the biggest threat of the violence broadcasted by the Lithuanian television programs.
Keywords: television broadcasting; physical and psychical violence; the effects of violence